2024
DOI: 10.1073/pnas.2307801120
|View full text |Cite
|
Sign up to set email alerts
|

Cationic cholesterol-dependent LNP delivery to lung stem cells, the liver, and heart

Afsane Radmand,
Hyejin Kim,
Jared Beyersdorf
et al.

Abstract: Adding a cationic helper lipid to a lipid nanoparticle (LNP) can increase lung delivery and decrease liver delivery. However, it remains unclear whether charge-dependent tropism is universal or, alternatively, whether it depends on the component that is charged. Here, we report evidence that cationic cholesterol-dependent tropism can differ from cationic helper lipid-dependent tropism. By testing how 196 LNPs delivered mRNA to 22 cell types, we found that charged cholesterols led to a different lung:liver deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Further, when incubated in mouse plasma, these nanoparticles showed a more significant increase in size putatively due to their association with proteins. The strategy of tuning charge ratio shares partial similarity with previous work on organ-tropic LNP systems, 13,14 in which the addition of cationic lipids promoted lung tropism while anionic lipids promoted spleen tropism. 16 However, neither the size nor the surface charge has been reported to be correlated with organ tropism in LNP systems, 14 suggesting that organ-targeting mechanisms for LNPs and CARTs could be different.…”
Section: ■ Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Further, when incubated in mouse plasma, these nanoparticles showed a more significant increase in size putatively due to their association with proteins. The strategy of tuning charge ratio shares partial similarity with previous work on organ-tropic LNP systems, 13,14 in which the addition of cationic lipids promoted lung tropism while anionic lipids promoted spleen tropism. 16 However, neither the size nor the surface charge has been reported to be correlated with organ tropism in LNP systems, 14 suggesting that organ-targeting mechanisms for LNPs and CARTs could be different.…”
Section: ■ Discussionmentioning
confidence: 69%
“…12 More recently, and somewhat unexpectedly, "passive targeting", based on the intrinsic properties of LNP−mRNA complexes, has shown considerable promise for organ-selective delivery. 13,14 For instance, the Sahin group has shown that liposome formulations with varied charge ratios (cationic lipid to anionic mRNA phosphates), upon i.v. administration, selectively transfect lungs and spleens.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation